Nitrogen-doped MXene-loaded VCo double-monatomic catalyst as well as preparation method and application of nitrogen-doped MXene-loaded VCo double-monatomic catalyst
By using nitrogen-doped MXene-loaded VCo dual-single-atom catalyst in room temperature sodium-sulfur batteries, the problems of low reversible capacity and poor cycle performance of the battery are solved, and efficient electrochemical performance improvement is achieved.
Patent Information
- Application Number
- CN202411501560.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-07
AI Technical Summary
In practical applications, room temperature sodium-sulfur batteries face problems such as low reversible capacity, poor self-discharge and cycle performance. In particular, the natural insulation of sulfur limits its application as an active material, resulting in slow kinetics of the cathode.
Using a VCo double-single atom catalyst based on nitrogen-doped MXene, the Vanadium single atom and cobalt single atom are independently dispersed and anchored on the support through nitrogen-doped MXene as a support, forming a synergistic catalytic effect and improving catalytic activity and electrochemical performance.
The electrochemical performance of room temperature sodium-sulfur batteries is significantly enhanced, including high reversible capacity and good cycle stability, and solves the bottleneck of RT/Na-S batteries.
Smart Images

Figure CN119581586A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrochemical energy storage, and relates to a nitrogen-doped MXene-loaded VCo double single-atom catalyst, and a preparation method and application thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly severe environmental problems, the search for efficient and sustainable energy storage technology has become a hot topic in scientific research. Room temperature sodium-sulfur batteries (RT / Na-S) are regarded as the next generation energy storage technology with broad application prospects due to their high theoretical energy density (1274Wh / kg) and abundant reserves and low cost of sodium and sulfur. However, RT / Na-S batteries still face challenges such as low reversible capacity, poor self-discharge and cycle performance in practical applications. In particular, the natural insulating property of sulfur limits its application as an active material, resulting in slow kinetics of the electrochemical process at the cathode.
[0003] In order to solve the above problems, researchers began to explore various improvement strategies in order to improve the overall performance of RT / Na-S batteries. MXenes, as a new type of two-dimensional material, are composed of transition metal carbides, nitrides or carbonitrides, and have the characteristics of high conductivity, large specific surface area and excellent chemical stability. In recent years, MXenes have shown great application potential in the fields of energy, catalysis, electromagnetic shielding, etc. In particular, modifying MXenes by nitrogen doping can regulate the electronic structure, chemical properties and surface characteristics of MXenes, thereby improving their performance; nitrogen doping can not only increase the active sites of MXenes and improve catalytic activity, but also improve their electromagnetic properties, expanding their application in electromagnetic shielding and other fields.
[0004] In addition, in the field of catalysts, single-atom catalysts have attracted widespread attention due to their high catalytic activity and selectivity, as well as the effective use of precious metals. At the same time, diatomic catalysts are also becoming a hot topic of research because they show better catalytic performance than single-atom catalysts and perform well in applications such as electrolysis of water to produce hydrogen and photoelectrocatalysis. However, there are currently few specific studies on the application of diatomic catalysts in RT / Na-S battery systems, which means that this field needs to be further explored and may provide new performance optimization methods for RT / Na-S batteries. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a nitrogen-doped MXene-loaded VCo double single-atom catalyst and a preparation method thereof, and explores its application in room-temperature sodium-sulfur batteries. Its application in room-temperature sodium-sulfur batteries shows excellent electrochemical performance.
[0006] One object of the present invention is achieved by the following technical solutions:
[0007] A VCo double single-atom catalyst based on nitrogen-doped MXene, wherein the catalyst uses nitrogen-doped MXene as a carrier, and vanadium single atoms and cobalt single atoms are independently and dispersedly anchored on the carrier. That is, copper atoms and cobalt atoms are anchored on the carrier in a monodispersed form.
[0008] Preferably, the loading amount of vanadium single atom and cobalt single atom is 0.1-3 wt %.
[0009] Loading amount = mass of vanadium single atom and cobalt single atom / total mass of catalyst*100%.
[0010] Preferably, the MXene is a few-layer MXene, which refers to a stacked structure containing two to dozens of MXene layers.
[0011] Vanadium single atoms and cobalt single atoms are independently and dispersedly anchored at least one place on the MXene surface, between adjacent MXene layers, etc.
[0012] Preferably, the molecular formula of the MXene is M n+1 X n T x , wherein M is one or more of Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, and Ta elements, X is C and / or N, T is a surface-attached functional group, and n is 1, 2, 3, or 4.
[0013] For example, T can be one or more of -Cl, -Br, -I, -F, -O, -OH, -S, and alkyl.
[0014] More preferably, the structural formula of the MXene is Ti n+1 C n T x .
[0015] The second object of the present invention is achieved by the following technical solutions:
[0016] A preparation method based on nitrogen-doped MXene-supported VCo double single-atom catalyst comprises the following steps:
[0017] (1) Preparation of few-layer MXene suspension;
[0018] (2) adding a nitrogen-containing precursor to at least one layer of the MXene suspension and stirring the mixture to obtain a suspension;
[0019] (3) dissolving a cobalt-containing compound and a vanadium-containing compound in water to prepare a cobalt-containing compound solution and a vanadium-containing compound solution respectively, and adding the solutions to the suspension, stirring, ultrasonicating, and crushing to obtain a mixed solution;
[0020] (4) freeze-drying the mixed solution to obtain a precursor; then heat-treating the precursor in a reducing atmosphere, washing, centrifuging, and drying the obtained powder to obtain the nitrogen-doped MXene-loaded VCo double single-atom catalyst.
[0021] Preferably, the preparation method of the few-layer MXene suspension comprises the following steps: adding lithium fluoride powder and MAX phase material powder to a hydrochloric acid solution and etching under stirring, centrifuging and washing to obtain a precipitate, dispersing the precipitate in a solvent, then ultrasonicating, centrifuging and obtaining a supernatant to obtain a few-layer MXene suspension.
[0022] In the method for preparing a few-layer MXene suspension, preferably, the molecular formula of the MAX phase material is M n+1 AX n , wherein the M element is the same as the M element in the molecular formula of the MXene, the X element is the same as the X element in the molecular formula of the MXene, the value of n is the same as the value of n in the molecular formula of the MXene, and A is one or more elements of the IIIA or IVA main group in the periodic table. Further preferably, the MAX phase material is Ti n+1 AlC n .
[0023] In the preparation method of the few-layer MXene suspension, the amount of lithium fluoride powder and hydrochloric acid should be appropriately excessive to achieve complete etching of the MAX phase material powder. Preferably, the concentration of the hydrochloric acid solution is 1 to 20 mol / L, and more preferably 6 to 12 mol / L. The stirring rate is kept at the maximum while ensuring that the solution does not splash. Preferably, the etching temperature is 25 to 50°C, and the etching time is 24 to 50 hours. After etching, centrifugation is performed, and the centrifugal speed at this time is preferably 3000 to 5000 rpm, and the time is preferably 1 to 10 minutes. The precipitate obtained by washing is dispersed in a solvent, and the solvent can be listed as water, ethanol, acetone, etc., and then the oscillator is oscillated for 1 to 10 minutes. Preferably, the ultrasonic time is 10 to 100 minutes. The centrifugal speed after ultrasound is preferably between 1500 and 2500 rpm, and the centrifugal time is 30 to 60 minutes.
[0024] Preferably, the concentration of the few-layer MXene suspension is 1 to 10 mg / mL.
[0025] Preferably, in step (2), the mass ratio of the nitrogen-containing precursor to the few-layer MXene is (3-5): (1-3). The stirring time is 5-30 min.
[0026] Preferably, the nitrogen-containing precursor includes one or more of melamine, urea, cyanamide, and dicyandiamide.
[0027] Preferably, in step (3), the concentrations of the cobalt-containing compound solution and the vanadium-containing compound solution are 1 to 10 mg / mL, respectively. The mass ratio of the cobalt-containing compound to the few-layer MXene can be 1:5 to 100, and the mass ratio of the vanadium-containing compound to the few-layer MXene can be 1:5 to 100. The stirring time is 10 to 60 min, the ultrasonic time is 10 to 60 min, and the crushing time is 5 to 20 min.
[0028] Preferably, the cobalt-containing compound is one or more of cobalt acetylacetonate, cobalt chloride and cobalt nitrate.
[0029] Preferably, the vanadium-containing compound is one or more of vanadium acetylacetonate, vanadium chloride and vanadium nitrate.
[0030] Preferably, in step (4), freeze drying is performed by freezing the mixed solution with liquid nitrogen for 1 to 20 minutes and then placing it in a freeze drying oven for 10 to 48 hours.
[0031] Preferably, in step (4), the reducing atmosphere is a mixture of H2 and Ar, wherein the volume percentage of H2 is 5-10%, and the gas flow rate of the mixture of H2 and Ar is 100-300 sccm.
[0032] Preferably, in step (4), the heat treatment step comprises: heating to 300-500° C. at a rate of 1-8° C. / min and keeping the temperature for 1-5 h.
[0033] The third object of the present invention is achieved by the following technical solutions:
[0034] A use of a nitrogen-doped MXene-loaded VCo double single-atom catalyst in a room-temperature sodium-sulfur battery, wherein the positive electrode material of the room-temperature sodium-sulfur battery comprises the nitrogen-doped MXene-loaded VCo double single-atom catalyst.
[0035] Preferably, the positive electrode material comprises a mixture of the nitrogen-doped MXene-loaded VCo double single-atom catalyst and sulfur powder in a mass ratio of 1:0.1 to 100; further, the mass ratio is 1:0.5 to 50; further, the mass ratio is 1:1 to 10.
[0036] Preferably, the positive electrode sheet of the room temperature sodium-sulfur battery comprises the positive electrode material, a conductive agent, and a binder, wherein the mass ratio of the positive electrode material, the conductive agent, and the binder is 70-90:5-15:5-15.
[0037] The present invention proposes a method for preparing a VCo double single-atom catalyst based on nitrogen-doped MXene. The preparation process of the catalyst includes the steps of preparing nitrogen-doped MXene, anchoring VCo double single atoms, and heat treatment. By precisely controlling the preparation conditions, efficient synthesis of the catalyst is achieved. Compared with the prior art, the method has the following beneficial effects:
[0038] (1) Efficient synthesis of catalysts: After mixed acid etching, a large number of defect sites and rich functional groups are generated on the surface of the few-layer MXene. The surface functional groups are optimized by N doping. Electrostatic adsorption and medium-temperature reduction treatment can effectively anchor V and Co double single atoms on MXene, thereby increasing the metal loading.
[0039] (2) Synergistic catalytic effect: The electronegativity of Co is greater than that of V, causing the electrons of V to flow to Co, making Co in an electron-rich state, thereby achieving a diatomic charge balance, which is beneficial to the catalytic reaction; the V and Co double single-atom catalyst combines the catalytic advantages of the two metals to achieve a synergistic effect. Based on their synergistic catalytic effect, the performance of room-temperature sodium-sulfur batteries is significantly enhanced.
[0040] (3) The VCo bimetallic single-atom catalyst combines the catalytic advantages of V and Co metals to achieve a synergistic effect. Loading the VCo bimetallic single-atom catalyst on nitrogen-doped MXene can not only fully utilize the high specific surface area and good conductivity of MXene, but also further regulate its surface chemical properties through nitrogen doping. This catalyst can innovatively serve as the host material for the sulfur positive electrode of room-temperature sodium-sulfur batteries, significantly enhancing the electrochemical performance of the battery, including high reversible capacity and good cycle stability, providing new ideas and technical support for solving the performance bottleneck faced by RT / Na-S batteries.
[0041] (4) The preparation method of the nitrogen-doped MXene-loaded VCo double single-atom catalyst of the present invention has a simple and feasible process, low cost, and is suitable for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a HADDF-STEM image of the nitrogen-doped MXene-supported VCo double single-atom catalyst prepared in Example 1 of the present invention;
[0043] Figure 2 This is a spherical aberration corrected high-resolution transmission electron microscopy image of the nitrogen-doped MXene-supported VCo double single-atom catalyst prepared in Example 1 of the present invention;
[0044] Figure 3The rate performance diagram of a room temperature sodium-sulfur battery using the nitrogen-doped MXene-supported VCo double single-atom catalyst prepared in Example 1 of the present invention and the catalyst prepared in Comparative Examples 1-3 as a sulfur host;
[0045] Figure 4 This is a long cycle curve diagram of the nitrogen-doped MXene-loaded VCo double single-atom catalyst prepared in Example 1 of the present invention and the catalysts prepared in Comparative Examples 1-3 as sulfur hosts in room temperature sodium-sulfur batteries. DETAILED DESCRIPTION
[0046] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0047] Example 1
[0048] This embodiment is a preparation method based on nitrogen-doped MXene-supported VCo double single-atom catalyst, and the preparation method comprises the following steps:
[0049] (a) 2.4 g lithium fluoride powder and 2 g titanium aluminum carbide Ti3AlC2 powder were added to 9 mol / L hydrochloric acid solution and etched at 700 r / min and constant temperature of 45 °C for 35 h, then centrifuged at 4000 rpm for 4 min, and washed six times to obtain a dark green precipitate; the dark green precipitate was dispersed in 240 mL of deionized water, oscillated on an oscillator for 5 min, then ultrasonically treated for 1 h, centrifuged at 1800 rpm for 45 min, and then the upper layer liquid was taken to obtain a few-layer MXene suspension (concentration of about 5 mg / mL);
[0050] (b) taking 30 mL of the above-mentioned few-layer MXene suspension, adding 300 mg of melamine to the at least-layer MXene suspension and stirring at 500 r / min for 30 min to obtain a suspension;
[0051] (c) weighing 20 mg of vanadium acetylacetonate and cobalt acetylacetonate powder respectively into a small glass bottle to prepare 2 mg / mL vanadium acetylacetonate solution and cobalt acetylacetonate solution; measuring 2 mL of vanadium acetylacetonate solution and 2 mL of cobalt acetylacetonate solution, adding them to the above suspension under magnetic stirring, stirring at a stirring rate of 700 rpm for 45 min, then ultrasonicating for 30 min, and finally crushing in an ultrasonic crusher for 10 min to obtain a uniform mixed solution;
[0052] (d) The mixed solution was frozen with liquid nitrogen for 5 min, and then placed in a freeze drying oven for 36 h for freeze drying to obtain a precursor, which was heat treated with a H2 / Ar mixed gas with a volume fraction of 5% at a ventilation rate of 100 sccm, and the temperature was increased to 450°C at a rate of 5°C / min and kept warm for 2 h. The obtained powder was washed with deionized water, centrifuged, and vacuum dried to obtain the above-mentioned nitrogen-doped MXene-supported VCo double single-atom catalyst (VCo-Ti3C2T x ), the loading amount of vanadium single atom and cobalt single atom is 0.85wt%.
[0053] Figure 1 and Figure 2 Here are the corresponding HADDF-STEM images and the high-resolution TEM images corrected for spherical aberration. Figure 1 It shows that the synthesized VCo-Ti3C2T x Still maintain the nanosheet morphology. Due to the nanosheet structure, VCo-Ti3C2T x The interlayer stacked mesopores are shown to enhance the accessibility of active sites and improve the overall catalytic performance of the material, with no visible metal particles.
[0054] Figure 2 a shows that single V and Co diatoms (indicated by sharp bright spots) are uniformly distributed on the N-doped MXene lattice stripes. In addition, the distances between three pairs of metal atoms in the randomly selected area are 0.27, 0.28, and 0.31 nm, respectively ( Figure 2 b). Based on the relationship between atomic number and contrast, it can be qualitatively inferred that the darker atomic dots represent V atoms, while the brighter atomic dots correspond to Co atoms.
[0055] Example 2
[0056] This embodiment is a preparation method based on nitrogen-doped MXene-supported VCo double single-atom catalyst, and the preparation method comprises the following steps:
[0057] (a) 2 g lithium fluoride powder and 1.5 g titanium aluminum carbide Ti3AlC2 powder were added to 7 mol / L hydrochloric acid solution and etched at 600 r / min and constant temperature of 40 °C for 40 h, then centrifuged at 3500 rpm for 3 min, and washed six times to obtain a dark green precipitate; the dark green precipitate was dispersed in 300 mL of deionized water, oscillated on an oscillator for 6 min, then ultrasonically treated for 50 min, centrifuged at 1500 rpm for 40 min, and the upper layer liquid was taken to obtain a few-layer MXene suspension (concentration of about 4 mg / mL);
[0058] (b) taking 25 mL of the above-mentioned few-layer MXene suspension, adding 260 mg of melamine to the few-layer MXene suspension and stirring at 500 r / min for 40 min to obtain a suspension;
[0059] (c) weighing 30 mg of cobalt nitrate and vanadium nitrate powder respectively into a small glass bottle to prepare 3 mg / mL cobalt nitrate solution and vanadium nitrate solution; measuring 2 mL of cobalt nitrate solution and 2 mL of vanadium nitrate solution, adding them to the above suspension under magnetic stirring, stirring at a stirring rate of 800 rpm for 50 min, then ultrasonicating for 50 min, and finally crushing in an ultrasonic crusher for 8 min to obtain a uniform mixed solution;
[0060] (d) The mixed solution was frozen with liquid nitrogen for 4 minutes, and then placed in a freeze drying oven for 40 hours for freeze drying to obtain a precursor, which was heat treated with a H2 / Ar mixed gas with a volume fraction of 6% at a ventilation rate of 200 seem, and the temperature was raised to 400°C at 4°C / min and kept warm for 2 hours. The obtained powder was washed with deionized water, centrifuged, and vacuum dried to obtain the above-mentioned nitrogen-doped MXene-loaded VCo double single-atom catalyst.
[0061] Application Example 1
[0062] This embodiment is an application of nitrogen-doped MXene-loaded VCo double single-atom catalyst in a room temperature sodium-sulfur battery, comprising the following steps:
[0063] (a) mixing sulfur powder and the nitrogen-doped MXene-supported VCo double single-atom catalyst in a mass ratio of 2:1 and grinding them evenly to obtain a composite cathode material;
[0064] (b) the composite cathode material, Ketjen black and PVDF binder are mixed and ground evenly in a mass ratio of 8:1:1, and NMP solvent is added to form a slurry with a certain viscosity, which is then coated on a single-glazed aluminum foil current collector;
[0065] (c) placing the coated electrode sheet in an oven at 45° C. and drying for 7 h to obtain a positive electrode sheet, which is then cut into discs with a diameter of 12 mm for assembling button batteries;
[0066] (d) The assembly of the button cell was completed in a glove phase filled with argon, with metallic sodium as the negative electrode, a glass fiber separator of model GF / D and a polyethylene of Celgard2400 as the battery separator, and 100 μL of 1 M NaSO3CF3 / DME electrolyte added;
[0067] (f) The assembled button cells were tested on the battery testing system LANDsystem7, with a voltage range of 0.4 to 3.0 V and current densities of 0.2, 0.5, 1.0 and 2.0 A / g, respectively. Figure 3 and Figure 4 They are the corresponding rate and long cycle performance diagrams respectively.
[0068] Comparative Example 1
[0069] Comparative Example 1: A nitrogen-doped MXene-supported Co single-atom catalyst (Co-Ti3C2T x ), the preparation method comprises:
[0070] Steps (a)-(b) and (d) are the same as in Example 1;
[0071] (c) 4 mL of 2 mg / mL cobalt acetylacetonate solution was added to the suspension, and the remaining operations were the same as step (c) of Example 1.
[0072] The catalyst of Comparative Example 1 is used as a sulfur host material for a room temperature sodium-sulfur battery and its battery assembly process is exactly the same as that of Application Example 1.
[0073] Comparative Example 2
[0074] Comparative Example 2: A nitrogen-doped MXene-supported V single-atom catalyst (V-Ti3C2T x ), the preparation method comprises:
[0075] Steps (a)-(b) and (d) are the same as in Example 1;
[0076] (c) 4 mL of 2 mg / mL vanadium acetylacetonate solution was added to the suspension, and the remaining operations were the same as step (c) of Example 1.
[0077] The catalyst of Comparative Example 2 is used as a sulfur host material for a room temperature sodium-sulfur battery and its battery assembly process is exactly the same as that of Application Example 1.
[0078] Comparative Example 3
[0079] Comparative Example 3: A nitrogen-doped MXene substrate material (Ti3C2T x ), the preparation method comprises:
[0080] Steps (a)-(b) and (d) are the same as in Example 1;
[0081] (c) 4 mL of water was added to the suspension under magnetic stirring, stirred at a stirring rate of 700 rpm for 45 min, then ultrasonicated for 30 min, and finally crushed in an ultrasonic crusher for 10 min to obtain a uniform mixed solution;
[0082] The nitrogen-doped MXene substrate material of Comparative Example 3 is used as a sulfur host material for a room-temperature sodium-sulfur battery and its battery assembly process is exactly the same as that of Application Example 1.
[0083] Figure 3 and Figure 4 The figures are respectively the rate and long cycle performance diagrams corresponding to the sodium-sulfur battery of Example 1 and the sodium-sulfur battery of Comparative Examples 1-3. Figure 3 It can be seen that S@VCo-Ti3C2T x (Application Example 1) The cathode exhibits excellent rate performance, with average capacities of 1255.3, 1190.6, 1176.6, 1161.9 and 1137.8 mAh g-1 at current densities of 0.1, 0.2, 0.5, 1.0 and 2.0 C, respectively. It is worth noting that even when the current density is restored to 0.2 C, the cathode can still provide a high capacity of 1201.7 mAh g-1. At all test rates, VCo-Ti3C2T x The rate capacity of the cathode significantly exceeds that of S@V-Ti3C2T x (Comparative Example 2) e and S@Co-Ti3C2T x (Comparative Example 1) Cathode.
[0084] like Figure 4 As shown, at a higher current density of 1.0C, S@VCo-Ti3C2T x The cathode exhibited excellent discharge capacity and cycle stability in long-term tests. The initial discharge capacity was 1215.7 mAh g1, and the capacity decay rate per cycle was about 0.001% over 1400 cycles. In comparison, S@V-Ti3C2T x and S@Co-Ti3C2T x The capacity decay rates of the cathode are approximately 0.008% and 0.009%, respectively.
[0085] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.
[0086] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.
[0087] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.
Claims
1. A nitrogen-doped MXene-supported VCo double single-atom catalyst, characterized in that: The catalyst uses nitrogen-doped MXene as a carrier, and single vanadium atoms and single cobalt atoms are independently and dispersedly anchored on the carrier.
2. The VCo double single-atom catalyst based on nitrogen-doped MXene according to claim 1, characterized in that: The MXene is a few-layer MXene; And / or, the molecular formula of the MXene is M n+1 X n T x , wherein M is one or more of Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, and Ta elements, X is C and / or N, T is a surface-attached functional group, and n is 1, 2, 3, or 4.
3. A method for preparing a nitrogen-doped MXene-supported VCo double single-atom catalyst, characterized in that: The preparation method comprises the following steps: (1) Preparation of few-layer MXene suspension; (2) adding a nitrogen-containing precursor to at least one layer of the MXene suspension and stirring the mixture to obtain a suspension; (3) dissolving a cobalt-containing compound and a vanadium-containing compound in water to prepare a cobalt-containing compound solution and a vanadium-containing compound solution respectively, and adding the solutions to the suspension, stirring, ultrasonicating, and crushing to obtain a mixed solution; (4) freeze-drying the mixed solution to obtain a precursor; then heat-treating the precursor in a reducing atmosphere, washing, centrifuging, and drying the obtained powder to obtain the nitrogen-doped MXene-loaded VCo double single-atom catalyst.
4. The preparation method according to claim 3, characterized in that: The preparation method of the few-layer MXene suspension includes the following steps: adding lithium fluoride powder and MAX phase material powder to a hydrochloric acid solution and etching under stirring, centrifuging and washing to obtain a precipitate, dispersing the precipitate in a solvent, then ultrasonicating, centrifuging and obtaining a supernatant to obtain a few-layer MXene suspension.
5. The preparation method according to claim 4, characterized in that: The molecular formula of the MAX phase material is M n+1 AX n , wherein the M element is the same as the M element in the molecular formula of the MXene, the X element is the same as the X element in the molecular formula of the MXene, the value of n is the same as the value of n in the molecular formula of the MXene, and A is one or more elements of the IIIA or IVA main group in the periodic table; and / or, the concentration of the hydrochloric acid solution is 1 to 20 mol / L; And / or, the etching temperature is 25 to 50° C., and the etching time is 24 to 50 hours; and / or, centrifuging after etching, with a centrifugal speed of 3000-5000 rpm and a time of 1-10 min; and / or, in the method for preparing a few-layer MXene suspension, the ultrasonication time is 10 to 100 min; And / or, in the method for preparing a few-layer MXene suspension, the centrifugal speed after ultrasound is 1500-2500 rpm, and the centrifugal time is 30-60 min.
6. The preparation method according to claim 3, characterized in that: The concentration of the few-layer MXene suspension is 1 to 10 mg / mL; and / or, in step (2), the mass ratio of the nitrogen-containing precursor to the few-layer MXene is (3-5): (1-3); and / or, the nitrogen-containing precursor comprises one or more of melamine, urea, cyanamide, and dicyandiamide; And / or, the cobalt-containing compound is one or more of cobalt acetylacetonate, cobalt chloride, and cobalt nitrate, and the vanadium-containing compound is one or more of vanadium acetylacetonate, vanadium chloride, and vanadium nitrate.
7. The preparation method according to claim 3, characterized in that: In step (3), the concentrations of the cobalt-containing compound solution and the vanadium-containing compound solution are each independently 1 to 10 mg / mL; And / or, the mass ratio of the cobalt-containing compound to the few-layer MXene is 1:5-100, and the mass ratio of the vanadium-containing compound to the few-layer MXene is 1:5-100.
8. The preparation method according to claim 3, characterized in that: In step (4), freeze drying is to freeze the mixed solution with liquid nitrogen for 1 to 20 minutes, and then place it in a freeze drying box for 10 to 48 hours; And / or, in step (4), the reducing atmosphere is a mixed gas of H2 and Ar, wherein the volume percentage of H2 is 5-10%; and the gas flow rate of the mixed gas of H2 and Ar is 100-300 sccm. And / or, in step (4), the heat treatment step comprises: heating to 300-500° C. at a rate of 1-8° C. / min and keeping the temperature for 1-5 hours.
9. Application of a nitrogen-doped MXene-supported VCo double single-atom catalyst in a room-temperature sodium-sulfur battery prepared by the preparation method according to claim 1 or claim 3, characterized in that: The positive electrode material of the room temperature sodium-sulfur battery includes the nitrogen-doped MXene-supported VCo double single-atom catalyst.
10. The use according to claim 9, characterized in that The positive electrode material includes a mixture of the nitrogen-doped MXene-supported VCo double single-atom catalyst and sulfur powder in a mass ratio of 1:0.1-100.
Citation Information
Cited By
Composite positive electrode material, preparation method, positive plate and sodium ion battery
CN120784349A
A composite cathode material, its preparation method, cathode sheet, and sodium-ion battery
CN120784349B
Loaded bimetal-based two-dimensional nano catalytic material as well as preparation method and application thereof
CN122076481A
Bimetallic-based two-dimensional nanocatalytic material, preparation method and application thereof
CN122076481B